Genetic diversity and morphological variation of the common chaffinch Fringilla coelebs in the Azores. (13th December 2013) - Rodrigues, Pedro; Lopes, Ricardo Jorge; Reis, Sandra; Resendes, Roberto; Ramos, Jaime Albino; Tristão da Cunha, Regina
<x xml:space="preserve">Abstract</x> We present new insights into the genetic diversity and phylogeography of the common chaffinch Fringilla coelebs from the Azores, based on sequences of mitochondrial and nuclear genes from 44 individuals and an outgroup/comparison of 44 birds from Madeira, the Canary Islands and the Continental Western Palearctic. To understand the level of concordance between the genetic data and morphometric variability we analysed eight morphometric characters from 413 adult living birds from all the Azores islands and compared the population genetic distances with quantitative morphometric traits. Our results indicate the occurrence of gene flow among the common chaffinch populations in the archipelago revealing the lack of current genetic structure within it and the existence of two co‐occurring lineages. Results also indicate the existence of morphometric differences among islands that could be due to ecological features instead of island isolation. This study also confirms the genetic distance among the common chaffinch populations within Macaronesia and between these archipelagos and the Continental Western Palearctic.